Tragverhalten von biegebeanspruchten Stahlmasten mit polygonalen Querschnitten - Reinke, Thomas (Berichte zum Stahl- und Leichtbau / Karlsruher Institut für Technologie, Versuchsanstalt für Stahl, Holz und Steine, Stahl- und Leichtbau, 2015)
This work deals with the bending moment capacity of thin-walled steel poles with polygonal sections. Based on experimental and numerical investigations the bearing behavior of steel poles in bending with polygonal sections with an arbitrary number of corners up to the transition from a polygonal section to a round section is presented. Thereby the bearing behavior as a shell and the influence of imperfections are considered.